2021
DOI: 10.1002/ijgo.13586
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of maternal body mass index with umbilical artery Doppler in pregnancies complicated by fetal growth restriction and associated outcomes

Abstract: Objective To evaluate the correlation between umbilical artery (UA) Doppler and its feasibility across categories of maternal body mass index (BMI; calculated as weight in kilograms divided by the square of height in meters) in the presence of fetal growth restriction (FGR). Methods A total of 1074 singleton pregnancies with suspected FGR on ultrasound examination between 24+0 and 36+0 weeks of pregnancy were reviewed. Evaluation of the UA Doppler was performed at 1‐ to 2‐weekly intervals. Abnormal UA Doppler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
2
0
1
Order By: Relevance
“…It has been reported that high‐risk fetuses with FGR will usually result in abnormal Doppler findings, most commonly seen in the umbilical artery 5,16 . The findings of the present study concur with this, the evolving low risk of the growers subgroup demonstrated by the normal umbilical artery Dopplers (Table 2).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It has been reported that high‐risk fetuses with FGR will usually result in abnormal Doppler findings, most commonly seen in the umbilical artery 5,16 . The findings of the present study concur with this, the evolving low risk of the growers subgroup demonstrated by the normal umbilical artery Dopplers (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…However, this is a limitation in our study as maternal BMI was only recorded at recruitment, and changes in weight were not accounted for. Low pregnancy weight and poor weight gain have been reported to negatively affect fetal growth, 7 as does high maternal BMI, 16,17 but this was not assessed among the “growers.” It may be valuable to examine this aspect of maternal weight gain in future studies to assess its influence on fetal growth dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Воспалительные и окислительные изменения в плаценте приводят к снижению митохондриального дыхания, выработке аденозинтрифосфорной кислоты в трофобласте и нарушению ее функции. Соответственно, материнское ожирение может рассматриваться как фактор риска ПН [22][23][24]. С другой стороны, исследование L. Sawant et al демонстрирует, что низкий индекс массы тела у беременных приводит к уменьшению диаметра и массы плаценты.…”
Section: интерпретация результатов исследованияunclassified